(untitled) (Global Journal of Management and Business Research, 2013)
Obviously the equity risk premium (ERP) is an important parameter in finance, more especially in fixing the cost of equity capital and giving values to assets. However, its estimation has challenged academics, analysts and other practitioners in the field of finance as to which of the estimation approaches presents the best result for practical application. It was also observed that most of the studies on this important aspect of finance have been mostly conducted in the developed stock markets with very little or none done on some of the emerging markets. With this in mind, the researcher was moved to place an emerging stock market on the map of researches on the ERP.